Subjective Well-Being of High School Students Belonging to Indigenous Peoples of the North as a Basis for Readiness to Choose a Profession - G. V. Kuhterina; E. A. Solov'eva; L. V. Fedina; M. V. Muravyeva (Russian State Vocational Pedagogical University, 2020)
Introduction.The preservation and well-being of the indigenous peoples of the Russian North is directly related to the national identity, the values for sustaining vital activities, the continuation and development of traditional crafts. Thus, the professional self-determination of the oncoming generation from the Russian North is the basis for the preservation of their national heritage.The aim of the present publication was to determine the subjective grounds for the formation of personal readiness to choose a profession among high school students studying and living in the Arctic.Methodology and research methods. the empirical base of the research was formed by the obtained data using psychodiagnostic tools. The indicators were the subjective well-being of schoolchildren and their readiness for professional selfdetermination. 119 high school students aged 14-17 from educational institutions of the Yamal-Nenets Autonomous District of the Tyumen Region and the city of Tyumen took part in the testing of these complex constructs. The statistical data analysis was carried out along with comparative and correlation analyses.Results. The research results show the interrelated differences between indicators of subjective well-being and readiness to choose a profession among indigenous high schools students of the Russian North and their non-indigenous peers. The analysis of the statistical validity of differences using the Student's t-test demonstrated that high school students of the indigenous minorities of the Russian North have higher rates of psycho-emotional stability. Also, they are more independent and optimistic about choosing a profession. The results of the correlation analysis revealed that indigenous high school students of the Russian North have certain advantages over their non-indigenous peers when coping with the challenges of choosing a career. For instance, indigenous high school students are much less dependent on the indicators of subjective well-being. Their stronger psycho-emotional response to harsh living conditions increases their motivation for early professional self-determination.Scientific novelty. The current study enhances the understanding of the influence of relationships between personal characteristics and subjective well-being on the readiness to choose a career by graduates of secondary schools located in the Arctic.Practical significance. The research findings and conclusions could be exploited in order to build up more accurate and targeted system of career guidance support for high school students of the indigenous peoples of the North, as well as for other nationalities living in harsh climatic conditions.